2015
DOI: 10.1007/s12038-015-9540-6
|View full text |Cite
|
Sign up to set email alerts
|

Bifidogenic effect of grain larvae extract on serum lipid, glucose and intestinal microflora in rats

Abstract: The main objective of this study was to investigate whether orally administered Korean grain larvae ethanol extract (GLE) had a bifidogenic effect in normal rats. Male Sprague-Dawley rats were divided into a negative control group (CO) and GLE orally administered (5.0, 7.0 and 9.0 mg/100 g body weight) groups. Thymus and spleen weights dosedependently increased by 128.58 percent and 128.58 percent, respectively, but abdominal fat decreased by 19.18 percent after GLE administration compared with that in the CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…40 For other types of putative prebiotics, reduction in Clostridium has been observed together with reduction in blood lipids. 41 In our experiment, reduction by GSPE of several taxa that belong to Firmicutes is accompanied with a reduction in butyrate, an energy source for colonocytes. Our results in fact show a positive correlation between butyric acid and several genera, that are reduced by GSPE (e.g.…”
Section: Discussionmentioning
confidence: 49%
“…40 For other types of putative prebiotics, reduction in Clostridium has been observed together with reduction in blood lipids. 41 In our experiment, reduction by GSPE of several taxa that belong to Firmicutes is accompanied with a reduction in butyrate, an energy source for colonocytes. Our results in fact show a positive correlation between butyric acid and several genera, that are reduced by GSPE (e.g.…”
Section: Discussionmentioning
confidence: 49%
“…Hepatic FXR has been proposed to play a central role in the feedback repression of the CYP7A1 gene ( 12 ) . However, the negative correlation between FXR and CYP7A1 was uncertainty ( 28 ) . Conversely, Musso et al ( 47 ) reported that FXR activates the bile acid synthesis by inducing CYP7A1.…”
Section: Discussionmentioning
confidence: 99%
“…Faeces were collected on the last 3 d of the experimental period, freeze-dried, and then milled for bile acid measurement ( 27 ) . On the last day of the experimental period, the rats were fasted overnight (12–14 h) and lightly anaesthetised with diethyl ether ( 28 ) . Their body weights were measured.…”
Section: Methodsmentioning
confidence: 99%
“…single dose) and twenty were chronic (medium to long term) interventions. Six studies (36,(56)(57)(58)(59)(60) were conducted on animals that were not affected by particular stresses. Among these, Kim and colleagues investigated any toxic effects of a skimmed powder obtained from Zophobas atratus on specific pathogen-free (SPF) Sprague-Dawley rats for a 2-week repeated-dose toxicity study.…”
Section: Effect Of Edible Insects In Animal and Human Studiesmentioning
confidence: 99%
“…A reduced level of immunoglobulins (IgA, IgM, IgG), blood glucose and TG, TC and LDL was reported. Furthermore, this treatment modified the composition of caecal organic acids, increasing their total quantity and the acetic and propionic acid level, whilst reducing butyric, isobutyric, valeric and isovaleric acid contents (58) .…”
Section: Effect Of Edible Insects In Animal and Human Studiesmentioning
confidence: 99%